Using Video Blog in Teaching English - Marzuki, Muhammad Jahid; Nurpahmi, Sitti (English Language Teaching for EFL Learners Journal, 2019)
The objective of the research is to find out whether or not video blog can improve the speaking ability of the students of English Education Department of FTK UINAM in academic year 2017/2018. The researcher applied pre-experimental method, with one group pretest and posttest design which employed speaking test to find out the students’ speaking performance in terms of accuracy. The sample consisted of 20 students used purposive sampling technique taken from the population of the second semester students of Sulawesi Flight. The result of the data analysis indicated that there was significant difference of students’ speaking performance before and after being trained through video blog. It is proved by result of statistical analysis of the level significance 0.05 with degree of freedom (df) = N-1 = 20-1 = 19 which indicated that t-test value of final score I speaking ability (13.309) was greater than t-table (2.093). Therefore, video blog can improve speaking performance of the students.